The overexpression of Rps14 in Lgr5+ progenitor cells promotes hair cell regeneration in the postnatal mouse cochlea - Jingru Ai; Pei Jiang; Jingyuan Huang; Hairong Xiao; Yanqin Lin; Mingchen Dai; Yintao Wang; Yuan Zhang; Mengyao Tian; Renjie Chai; Shasha Zhang (Engineered Regeneration, 2023)
Sensory hair cells (HCs) in the cochlea cannot regenerate spontaneously in adult mammals after being damaged by external or genetic factors. However, several genes and signaling pathways are reported to induce cochlear HC regeneration at the early neonatal stage. Rps14 encodes a ribosomal protein that is involved in the regulation of cell differentiation and proliferation in mammals. However, its roles in the cochlea have not been reported in vivo. Here, we specifically overexpressed Rps14 in Lgr5+ progenitor cells in the newborn mouse cochlea and found that Rps14 conditional overexpression (cOE) mice had significantly increased the ectopic HCs, including inner and outer HCs. We further explored the source of these ectopic HCs and found no EdU+ supporting cells observed in the Rps14 cOE mice. The lineage tracing results, on the other hand, revealed that Rps14 cOE mice had significantly more tdTomato+ HCs in their cochleae than control mice. These results indicated that regenerated HCs by cOE of Rps14 are most likely derived from inducing the direct trans-differentiation of Lgr5+ progenitor cells into HCs. Moreover, real-time qPCR results suggested that the transcription factor genes Atoh1 and Gfi1, which are important in regulating HC differentiation, were upregulated in the cochlear basilar membrane of Rps14 cOE mice. In summary, this study provides in vivo evidence that, in the postnatal mouse cochlea, Rps14 is a potential gene that can promote the spontaneous trans-differentiation of Lgr5+ progenitor cells into HCs. This gene may one day be exploited as a therapeutic target for treating hearing loss.